Dabigatran etexilate – a novel, reversible, oral direct thrombin inhibitor: Interpretation of coagulation assays and reversal of anticoagulant activity - Ryn, Joanne van; Stangier, Joachim; Haertter, Sebastian; Liesenfeld, Karl-Heinz; Wienen, Wolfgang; Feuring, Martin; Clemens, Andreas (Thrombosis and Haemostasis, 2010)
Dabigatran etexilate is an oral, reversible direct thrombin inhibitor that is approved in the EU and several other countries for the prevention of venous thromboembolism after elective hip and knee replacement, and is in advanced clinical development for other thromboembolic disorders. Dabigatran has a predictable pharmacokinetic profile, allowing for a fixed-dose regimen without the need for routine coagulation monitoring. In certain clinical situations such as serious bleeding into critical organs (e.g. intracerebral bleeding), potential overdose and emergency surgery, clinicians will need to make an assessment of the anticoagulant status of a patient receiving dabigatran before deciding on future management strategies. If available, thrombin clotting time (TT), ecarin clotting time (ECT) and TT determined by Hemoclot→ thrombin inhibitor assay are sensitive tests to evaluate the anticoagulant effects of dabigatran. Prothrombin time (INR) is less sensitive than other assays and cannot be recommended. The activated partial thromboplastin time (aPTT) can provide a useful qualitative assessment of anticoagulant activity but is less sensitive at supratherapeutic dabigatran levels. There are limited data for activated clotting time (ACT). Overall, the aPTT and TT are the most accessible qualitative methods for determining the presence or absence of anticoagulant effect. Although there is no specific antidote to antagonise the anticoagulant effect of dabigatran, due to its short duration of effect drug discontinuation is usually sufficient to reverse any excessive anticoagulant activity. In case of potential overdose, the feasibility of early administration of activated charcoal and subsequent charcoal filtration are undergoing preclinical evaluation. Dabigatran can also be dialysed in patients with renal impairment. In instances of life-threatening bleeding, where conventional measures have failed or are unavailable, other non-specific prohaemo -static agents such as recombinant activated factor VII and prothrombin complex concentrates can be considered.Disclosure statement: All authors are employees of Boehringer Ingelheim.Figure 1 has been corrected in this version of the article.
Keywords: Dabigatran etexilate; dabigatran; direct thrombin inhibitor; coagulation assays; reversal